No Task Fit for a Soldier? Canadian Forces Medical Personnel and Humanitarian Relief Missions since the Second World War - Rawling, Bill (Scientia Canadensis, 2002)
AbstractModern armies of the industrialized world operate in accordance with a doctrine, that is to say a philosophy linked to a series of procedures themselves determined by the tactical and strategic environment. These same armies, however, answer to civilian governments that do not limit their demands or instructions to the types of operations an army might list in its doctrine. For Canada's armed services, such seems to have been the case in regards to humanitarian operations which, even if they were not part of these services' operational philosophies, have nonetheless been of no little importance in the history of the air force, the navy, and the army since the end of the Second World War. This study will explore humanitarian operations from the second half of the 1940s to the formation and first missions of a unit specializing in such work in the 1990s. It will focus mainly on medical practice during these missions and attempt to determine whether medical practitioners had to change their basic approach to accomplish their tasks, or whether it sufficed to adapt procedures in accordance with the operational situation.